Effect of microwave air spouted drying arranged in two and three-stages on the drying uniformity and quality of dehydrated carrot cubes. (May 2016) - Huang, Jiapeng; Zhang, Min; Adhikari, Benu; Yang, Zaixing
Abstract: Microwave air spouted drying arranged in two and three-stages was used to improve the drying uniformity, energy efficiency and product quality (color, aroma, taste and rehydration capacity) of carrot cubes. The two and three-stage drying arrangements were designed making use of the information obtained from drying curves of single-stage microwave air spouted drying. The carrot cubes dried using the two and three-stage microwave air spouted drying had retention of color, chlorophyll and carotenoids contents and higher rehydration capacity. They also had better drying uniformity in terms of moisture content, product temperature and sample size. The two and three-stage drying arrangements had significantly higher material loading capacity and energy utilization ratio. The carrot cubes dried using these two drying arrangements had better flavor and taste after drying as well as after rehydration. Thus the two and three-stage arrangements had advantages over single-stage microwave air spouted drying in terms of product quality and energy efficiency. Highlights: Multi-stage microwave air spouted drying systems were designed to improve the drying performance. Uniformity of surface temperature was measured using thermal imaging. Flavor and taste were evaluated using electronic nose and electronic tongue, respectively. Uniformity was greatly improved in terms of color moisture, temperature and sample size. Taste of the dried carrots was improved while the flavor was slightly deteriorated.